2000
DOI: 10.1086/317133
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Iron K Line in the Spectrum of the Galactic X‐Ray Background

Abstract: We propose a mechanism for the origin of the Galactic ridge X-ray background that naturally explains the properties of the Fe K line, speciÐcally the detection of the centroid line energy below 6.7 keV and the apparent broadness of the line. Motivated by recent evidence of nonthermal components in the spectrum of the Galactic X-ray/c-ray background, we consider a model that is a mixture of thermal plasma components of perhaps supernova origin and nonthermal emission from the interaction of low-energy cosmic-ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 32 publications
2
129
0
Order By: Relevance
“…The non-thermal radiation associated with the AC is most likely attributed to the presence of a sea of cosmic rays permeating the whole region within the cluster and the surroundings; Valinia et al (2000) showed that the diffuse emission from the Galactic ridge can be explained in terms of low energy cosmic rays (LECRs) producing both the continuum and the low ionization lines from the different elements. However, the slope of the non-thermal continuum emission found by these authors is about 1.3-1.4, somewhat steeper than the value we adopt.…”
Section: Discussionmentioning
confidence: 99%
“…The non-thermal radiation associated with the AC is most likely attributed to the presence of a sea of cosmic rays permeating the whole region within the cluster and the surroundings; Valinia et al (2000) showed that the diffuse emission from the Galactic ridge can be explained in terms of low energy cosmic rays (LECRs) producing both the continuum and the low ionization lines from the different elements. However, the slope of the non-thermal continuum emission found by these authors is about 1.3-1.4, somewhat steeper than the value we adopt.…”
Section: Discussionmentioning
confidence: 99%
“…The extended characteristic 6.4 keV line emission from low charge states of Fe being naturally produced by fluorescent scattering of the X-rays may be also excited by the low energy cosmic rays penetrating into molecular clouds in the vicinity of particle acceleration sites (see, e.g., Valinia et al 2000, Dogiel et al 2011a, Tatischeff et al 2012. Fast moving metal rich fragments of supernova ejecta may be sources of both 6.4 keV Fe line emission as well as the high charge state Fe K-shell lines in 6.7-6.9 keV range (Bykov 2002.…”
Section: Galactic Center Clustersmentioning
confidence: 99%
“…This model was proposed by Valinia et al (2000) to account for the X-ray spectrum and the 6.4 keV line emission from the large-scale Galactic ridge, and was adopted by YusefZadeh, Law & Wardle (2002) to explain the unusual brightness of the 6.4 keV line in the G0.11-0.11 (also known as G0.13-0.13) molecular cloud in the Galactic center (Park et al 2004), which is apparently interacting with relativistic particles in the Galactic center Radio Arc. Yusef-Zadeh, Law & Wardle (2002) suggested that the same mechanism might be applicable to 6.4 keV line sources elsewhere in the Galactic center.…”
Section: X-ray Fluorescence In the Galactic Center: Echo Of A Recent mentioning
confidence: 99%